Can policies improve language vitality? The Sámi languages in Sweden and Norway - Lloyd-Smith, Anika; Bergmann, Fabian; Hund, Laura; Kupisch, Tanja (Frontiers in Psychology, 2023)
Language policies are often aimed at changing patterns in language behaviours and attitudes. Yet while positive benefits of such policies tend to be assumed, it remains difficult to assess their effects. The Sámi languages in Sweden and Norway provide an interesting case, since both countries are viewed as prime examples of egalitarian welfare states, but differ in terms of the policies they have adopted, with Norway typically considered the more favourable environment for the Sámi. Surprisingly little is known about the existing levels of language use and proficiency amongst the Sámi, since most studies rely on small samples, and on self-reported rather than objective measures. In this article, we provide a cross-country comparison of the relevant educational, linguistic and budgetary policies in both states. Next, we present novel data from a survey with 5,416 Sámi and non-Sámi participants in 20 northern municipalities, examining Sámi language use and proficiencies across generations and contexts. We find that one fifth of Sámi adults today use a Sámi language at least ‘occasionally’, and that language use is highest in the home context. Though a small proportion of highly fluent speakers exists (around 4% of Sámi in Sweden and 11% in Norway), more work is needed to increase proficiencies in today’s speakers – also in the majority population. Finally, levels of language use and proficiency are significantly higher in Norway, which seems at least in part to reflect the more favourable policies implemented there.